Case report: The evolving phenotype of ESCO2 spectrum disorder in a 15-year-old Malaysian child - Tae, Sok-Kun; RA, Mazlan; Thong, Meow-Keong (Frontiers in Genetics, 2024)
ESCO2 spectrum disorder is an autosomal recessive developmental disorder characterized by growth retardation, symmetrical mesomelic limb malformation and distinctive facies with microcephaly, with a wide phenotypic continuum that ranged from Roberts syndrome (MIM #268300) at the severe end to SC phocomelia (MIM #269000) at the milder end. ESCO2 encodes a 601-amino acid protein belonging to the Eco1/Ctf7 family of acetyltransferases that is involved in the establishment of sister chromatid cohesion which is essential for accurate chromosome segregation and genomic stability and thus, belongs to a group of disorders called "cohesinopathies".We describe a 15-year-old Malaysian female who presented with the characteristic triad of ESCO2 spectrum disorder with equivocal chromosomal breakage study and normal karyotyping findings. She was initially suspected to have mosaic Fanconi anemia but whole exome sequencing (WES) showed a likely pathogenic homozygous splice variant c.955+2_955+5del in the ESCO2. During the 15-year diagnostic odyssey, she developed type 2 diabetes mellitus, primary ovarian insufficiency, increased optic cupto-disc ratio with tortuous vessels bilaterally and an evolving but distinct facial and skin hypopigmentation phenotype. Of note, there was absence of learning disabilities. Our findings provide further evidence for ESCO2 spectrum disorder in an Asian child and contribute to defining the clinical and radiographic spectrum.